PENINGKATAN KEMAMPUAN GURU DALAM MENGELOLA PEMBELAJARAN PERBAIKAN (REMEDIAL TEACHING) MATA PELAJARAN PENJASORKES MELALUI PEER COACHING DI SMP BINAAN KOTA BANDA ACEH - Budi Raharjo (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
Complete the learning approach is an effort in education that aim to motivate students to achieve mastery (mastery level) to a specific competency. By placing accomplished learning (mastery learning) as one of the key principles in support of the implementation of the implementation of the curriculum in 2013, which means that learning is something that should be thoroughly understood and implemented properly by all citizens, especially school education and other education personnel. Therefore, the need for guidelines to provide direction and guidance for education and educators in school about how learning should be implemented thoroughly. To achieve and meet the passing grade is the next step in the learning process improvement (remedial teaching). The aim of this study is to improve the ability of teachers in managing the learning improvement (remedial teaching) to achieve mastery learning (mastery learning) after implementing Peer Coaching. The subjects of this school is the teacher penjasorkes Kota Bharu City Junior High School number 6. Data collection was conducted in the following manner: interviews, questionnaires, observation, and recording. The results showed that the Peer Coaching or training peer undertaken in Kota Bharu City Junior High School have been able to improve the ability of teachers to implement instructional improvement. Peer Coaching, led by one of the teachers driver was able to motivate teachers in school Bandar Kota Bharu in planning and implementing improvements learning (Remadial Teaching). The statement has a significant impact on improving the quality of learning in Secondary Schools Bandar Kota Bharu. Peer Coaching has also been able to improve the competence of teachers of Junior High School in Bandar Kota Bharu choose the right model for learning in school improvement, especially in the implementation of the subjects Penjasorkes.